Prevalence of Undernutrition among Preschool Children (3-6 Years) Attending Anganwadi Centers in Urban Mysuru - Preetha Susan George; M. R. Narayana Murthy (Indian Journal of Medical Specialities)
Introduction: For balanced growth and childhood development, adequate nutrition is very necessary. The health and nutritional status of children is an indicator of the health and nutrition of the community and the nutritional profile of the entire country. Undernutrition is not only a significant cause of childhood morbidity and mortality, but it jeopardizes physical as well as mental development of children. The Public Distribution Scheme's bias toward calories and subsidies continued on rice and wheat and did not include more diverse and nutritious foods. Aims and Objectives: This study aims to determine the prevalence of undernutrition among preschool children (3–6 years) attending Anganwadi in Urban Mysuru. Materials and Methods: This community-based cross-sectional study was carried out in the field practice area of Bannimantap Urban Primary Health Centre for a period of 1 year. A total of 365 children (3–6 years) were included in the study. Required total sample size of 365 children in the age group of 3–6 years was selected from each Anganwadi as per population proportionate to size sampling technique. A pretested, semi-structured proforma was used to collect data pertaining to sociodemographic variables, maternal-related variables, and child-related variables. Data were coded and entered into MS Excel 2016 and analyzed using SPSS Version 22. Results: Among the total 365 children aged 3–6 years, 54.7% were males and 45.3% were females. Majority (60.8%) of the children hailed from nuclear family and 50% belonged to upper lower socioeconomic class. The prevalence of undernutrition which constitutes underweight, stunting, and wasting was 25.4%, 23.5%, and 10.2%, respectively. Prevalence of severe acute malnutrition was 0.3%. Conclusion: Lack of socioeconomic development along with ignorance of cost-effective nutritional diet intake contributed to undernutrition in our study area.